A critical analysis of the legal framework on animal feed in Malaysia: with special reference to the Feed Act 2009 - Saidin, Nurulaina; Abd Rahman, Fadilah; Abdullah, Noriham (International Journal of Engineering and Technology, 2018)
In the halal food supply chain, animal feed is an essential element which has direct implication for the safety, quality and halal integrity of animal-based food products. Comprehensive monitoring and control in the preparation, production, storage, and distribution of the animal feed are needed to ensure acceptable quality standard. Matters related to the importation, manufacture, sale and uses of feed and feed additive in Malaysia is regulated under the Feed Act 2009 and its regulations. This Act is introduced to ensure the quality and safety of feed by controlling the importation, manufacture, sale, and uses of feed and feed additive. In the context of animal feed in Malaysia, this paper seeks to highlight and examine its legal framework, focusing on the analysis of the Feed Act 2009. This study utilises qualitative approach using library research. The findings of the study demonstrate that, despite the existence of a specific law governing the animal feed activities, there is no provision addresses the issue of halal in the ingredients, preparation, production, storage, and distribution of animal feed. It is therefore suggested that a halal standard for animal feed preparation, production, storage, and distribution is further be developed to enhance the production of halal and safe animal feed in Malaysia.Â Â